2017
DOI: 10.1098/rsta.2016.0260
|View full text |Cite
|
Sign up to set email alerts
|

Cometary dust: the diversity of primitive refractory grains

Abstract: Comet dust is primitive and shows significant diversity. Our knowledge of the properties of primitive cometary particles has expanded significantly through microscale investigations of cosmic dust samples (anhydrous interplanetary dust particles (IDPs), chondritic porous (CP) IDPs and UltraCarbonaceous Antarctic micrometeorites, Stardust and Rosetta), as well as through remote sensing (Spitzer IR spectroscopy). Comet dust are aggregate particles of materials unequilibrated at submicrometre scales. We discuss t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 263 publications
(850 reference statements)
1
40
0
Order By: Relevance
“…This kind of materials were found in cometary comae particles together with CC, as shown by remote or in-situ observations (see e.g. Wooden et al, 2017). Our past and present laboratory measurements with PROGRA2 (Hadamcik et al, 2007a;2009b) have shown the importance of the presence of carbonaceous particles when trying to simulate cometary particles (with a global low-albedo).…”
Section: Similar Polarimetric Phase Curves and Reliability Of A Samplesupporting
confidence: 63%
See 1 more Smart Citation
“…This kind of materials were found in cometary comae particles together with CC, as shown by remote or in-situ observations (see e.g. Wooden et al, 2017). Our past and present laboratory measurements with PROGRA2 (Hadamcik et al, 2007a;2009b) have shown the importance of the presence of carbonaceous particles when trying to simulate cometary particles (with a global low-albedo).…”
Section: Similar Polarimetric Phase Curves and Reliability Of A Samplesupporting
confidence: 63%
“…Their precise composition (relative ratio of different elements, structure of the grains in the particles) can give some insight on their origin in the early solar system. The main technique to access their composition is remote or in-situ infrared spectroscopy compared to laboratory studies of collected particles (Hanner and Bradley, 2004 and references therein;Wooden et al, 2017). Cometary dust represents an un-equilibrated, heterogeneous mixture of crystalline and glassy or amorphous silicate minerals, organic refractory materials, and other constituents such as iron sulphide and possibly minor amount of iron oxides.…”
Section: Composition Of Interplanetary Dust Particlesmentioning
confidence: 99%
“…Wooden et al. () recently tied together several lines of evidence pointing to late formation of Wild 2 materials, several Mya the onset of CAI formation. These include an abundance of objects with O isotopic signatures close to the terrestrial value, and an overabundance of late stage objects including Fe‐rich type II chondrules, and late 26 Al dates (Ogliore et al.…”
Section: Discussionmentioning
confidence: 99%
“…Diane Wooden (NASA Ames Research Center) presented her overview on the diversity of primitive cometary dust particles and their implications for understanding conditions in the early Solar System [34]. Karl Battams (Naval Research Laboratory, USA) addressed the topic of objects that experience extreme conditions: sungrazers and sunskirters that venture much closer to the Sun than most comets that are observed from the Earth [35].…”
Section: Topics and Themes Coveredmentioning
confidence: 99%